Falloff Curves of the Reaction CF₃ (+M) → CF₂ + F (+M) - Cobos, Carlos Jorge (2020)
The thermal dissociation reaction CF₃ (+Ar) → CF₂ + F (+Ar) was studied in incident and reflected shock waves by monitoring UV absorption signals of the primary dissociation product CF₂. CF₃ radicals were produced by thermal decomposition of CF₃I. Accounting for secondary reactions of F atoms, rate constants for the unimolecular dissociation were derived. Experimental parts of the falloff curves were obtained over the ranges 1544 – 2106 K and 1.0 × 10⁻⁵ ≤ [Ar] ≤ 9.3 × 10⁻⁵ mol cm⁻³. Theoretical modelling allowed for a construction of the full falloff curves connecting the limiting low pressure rate constants k₀ = [Ar] 2.5 × 10¹⁸ (T/2000 K)-5.1 exp (-42 450 K/T) cm³ mol⁻¹ s⁻¹ with the limiting high pressure rate constants k∞ = 1.6 × 10¹⁶ (T/2000 K)-1.3 exp (-43 250 K/T) s⁻¹ (center broadening factors of Fcent= 0.25, 0.22, and 0.20 at 1500, 2000, and 2500 K, respectively, were used). The influence of simplifications of falloff expressions and of limiting rate constants on the representation of experimental data is discussed.